Let's break down the transformation of the function \( f(x) = 3^x \) to \( -f(3x - 2) + 1 \) step by step, listing each operation in order, and evaluating them sequentially for \(x = 1\), \(x = 2\), and \(x = 3\).
The new function is:
\[ g(x) = -f(3x - 2) + 1 = -3^{3x - 2} + 1 \]
We will create a table to display the order of operations and how it transforms the input step by step.
Table
| x | Step 1 | Step 2 | Step 3 | Step 4 | Step 5 | |---|----------------------|-----------------------|----------------------|---------------------|-----------------------------| | 1 | \( 3^{3(1) - 2} \) | \( 3^{3 - 2} \) | \( 3^1 \) | \( 3 \) | \( -3 + 1 = -2 \) | | 2 | \( 3^{3(2) - 2} \) | \( 3^{6 - 2} \) | \( 3^4 \) | \( 81 \) | \( -81 + 1 = -80 \) | | 3 | \( 3^{3(3) - 2} \) | \( 3^{9 - 2} \) | \( 3^7 \) | \( 2187 \) | \( -2187 + 1 = -2186 \) |
Explanation of Each Step:
- Step 1: Calculate \( 3(1) - 2 \), \( 3(2) - 2 \), or \( 3(3) - 2 \). This gives us \( 3x - 2 \).
- Step 2: Substitute the result from Step 1 into \( f(x) = 3^{3x - 2} \).
- Step 3: Evaluate the power of 3.
- Step 4: This final result is \( -3^{3x - 2} \) without the "+ 1".
- Step 5: Add \( 1 \) to the result from Step 4.
Thus, we successfully transformed \( f(x) = 3^x \) into \( -f(3x - 2) + 1 \) through these operations.